INTEGRASI FIQH SIYASAH DALAM PRINSIP KEDAULATAN RAKYAT: STUDI TERHADAP PEMILU DI INDONESIA - Mutiara Putri (TAHKIM, 2025)
This article examines the integration of Fiqh Siyasah in the principle of popular sovereignty in the context of general elections in Indonesia. In a democratic system, sovereignty is in the hands of the people, and elections are one of the main instruments to realize this principle. Democracy can be interpreted as people and power, democracy can also provide an understanding of a people's power, which is from the understanding obtained will provide a rule that can provide benefits and can protect their rights so that it can be implemented. This article focuses on the analysis from the perspective of Fiqh Siyasah on various important elements such as elections, popular sovereignty, election organizers, and dispute resolution of election results. Using the Fiqh Siyasah approach, this article seeks to understand how Sharia principles can be integrated with the modern democratic system, especially in the context of elections in Indonesia. Keywords: elections, people's sovereignty, fiqh siyasah.